Change in Hemoglobin Levels due to Anesthesia in Mice: An Important Confounder in Studies on Hematopoietic Drugs - Gothelf Anita; Hojman Pernille; Gehl Julie (Biological Procedures Online, 2009)
Abstract Analgesic and anesthetic drugs may have an impact on the results achieved from animal experiments. In the study presented here, we try to enlighten whether anesthesia with fentanyl/fluniasone and midazolam (Hypnorm and Dormicum) has an influence on measurements of hemoglobin in mice. In a cross-over study, we have compared hemoglobin levels in two groups of mice: anesthetized versus non-anesthetized and found significant decrease in hemoglobin levels in the anesthetized group (p < 0.05) unrelated to which group received the anesthesia. The mean hemoglobin levels after intraperitoneal administration of Hypnorm and Dormicum was 8.7 mmol/L compared to mean hemoglobin 9.9 mmol/L before anesthesia (p < 0.001), and the decrease lasted for more than 30 min. These results show that anesthesia can be an important confounder in studies involving measurements of hemoglobin, and this should be taken into account when planning studies and analyzing data.